Parametric investigation and year round performance of a novel passive multi-chamber vertical solar diffusion still: Energy, exergy and enviro-economic aspects. (15th November 2020) - Sharon, H.; Reddy, K.S.; Gorjian, Shiva
Graphical abstract: Highlights: Thermo-enviro-economic modeling of novel passive multi chamber vertical diffusion still. East-west manually tracked unit is superior than sole south oriented unit. Yield, exergy efficiency and performance ratio of about 11.13 kg/m 2 -d, 23.15% and 2.0. Mitigation of 67.9 tons of CO2 emission in 20 Yr life time. Low distillate production cost of about 0.90 INR/L. Abstract: Multiple-effect solar distillation units are more promising in fulfilling the potable water demands of population in rural and remote areas. Among multiple-effect distillation units, diffusion type is more compact, portable and high productive. In the present study, a novel type of passive multi-chamber vertical solar diffusion still is proposed and the impact of various system and climatic parameters on its performance and economics has been evaluated and presented. Triple chamber vertical diffusion still is found economical and it has a performance ratio and exergy efficiency of around two and 23.15%, respectively. Exposing the aperture of distillation unit to wind flow revealed a negative impact on its yield but the reverse is observed when the last condensing unit is exposed to the wind. Lower distillation and exergy efficiency is observed for 1st diffusion chamber compared to other chambers due to increased heat loss from absorber plate. Evaporative heat transfer ratio of diffusion chambers increased from 0.81 to 0.97 with increase in solar radiation intensity from 100 to 1000 W/m 2 . The optimized unit is simulated under the climatic conditions of various locations of Tamil Nadu state of India under sole south orientation and east-west manually tracked mode. Annual average yield of 11.13 kg/m 2 d is obtained with an exergy efficiency of 13.85% for east-west manually tracked unit. Distillate production cost and financial payback time of the unit are estimated to be 900.00 INR/kL and 0.63 Year, respectively. The proposed unit also has a capability to mitigate 67.93 tons (average) of CO2 emission during its 20 Year lifetime. Better yield, low distillate production cost and huge environmental benefits justify the capability of proposed triple chamber passive vertical solar diffusion still for sustainable desalination in under privileged/developing countries.